A new deal for Asia - Mahathir bin Mohamad, 1925- (Pelanduk Publications, 1999)
Talks about some pretty mind blowing stuff about the modern international economic system. It gives you a new way to look at the international affairs and specially capitalism. Author has given some amazing ideas as to how we can make it better.